Terapia wysiękowej postaci zwyrodnienia plamki związanego z wiekiem: stan obecny i perspektywy - Figurska, Małgorzata; Stankiewicz, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Age-related macular disease (ARMD) is affecting the central part of the retina. ARMD has two major forms: the dry type and the wet type. Although wet type comprises only 15% of ARMD, it is responsible for 90% of severe visual impairment in all ARMD cases. The problem is effective treatment of ARMD, above all its wet type. Laser therapy, retina surgery, TTT and local radiotherapy did not give expected results. The aim of this article is to present modern trends of wet type ARMD therapy, including pharmacotherapy and photodynamic therapy (PDT) in relation to pathobiology of choroidal neovascularization (CNV). The goals of pharmacotherapy were discussed in support, that choroidal neovascularization is a dynamic evolution, which includes initiation, active inflammation and non active involution. Cellular mechanisms of photodynamic therapy were presented. It is necessary to accentuate that in the future it can be a combination between PDT and pharmacotherapy, which inhibits early stage mediators of all types CNV and limits inflammation attendant CNV. These therapeutic approaches ere more likely succeed and included wide spectrum of wet ARMD pathogenesis. The clinical studies show that may be soon we will treat wet form of ARMD using angiostatic steroids, anti-VEGF monoclonal antibodies and anti-VEGF aptamers.